Eukoenenia ibitipoca: the first troglobitic Palpigradi (Arachnida) from a quartzitic cave - Souza, Maysa Fernanda Villela Rezende; Ferreira, Rodrigo Lopes (Zootaxa, 2019)
Although the arachnids of the order Palpigradi are very common in subterranean habitats, no species has yet been recorded from siliciclastic caves. During a survey of cave invertebrates conducted in quartizitic caves in southern Minas Gerais state (Brazil), the occurrence of a new troglobitic palpigrade was revealed. Accordingly, in this paper we describe Eukoenenia ibitipoca sp. nov. which is readily distinguished from most species of this genus by the presence of eight pairs of setae on propeltidium.